The Resolution of Contradictory Evidence Through the Method of Al-Jam’u Wa Al-Taufiq and Naskh - Athiyyah, Vina Sa'adatul; Haris, Muhammad (Al Irsyad: Jurnal Studi Islam, 2024)
Humans are endowed with reason and divine revelation as guidance for implementing Sharia law. A mujtahid resolves conflicting pieces of evidence (ta’arudh al-adillah) through methods such as al-jam’u (reconciliation), tarjih (preference), nasakh (abrogation), or tawaquf (suspension), depending on the school of thought and theological context. This study aims to examine the methods of al-jam’u wa at-taufiq and nasakh to understand how Islamic scholars, particularly from the Shafi’i and Hanafi schools, resolve contradictions between evidence. This research adopts a qualitative approach, using literature review methods to analyze sources and data on resolving conflicting evidence in Islamic law. The study finds that among the methods offered is an attempt to gather and reconcile seemingly contradictory evidence to reach a balanced ruling. This method is known as al-jam’u wa at-taufiq. Additionally, nasakhis were employed, which involves the annulment or replacement of one evidence with another, focusing on the chronological order of revelation. Conclusion: Al-jam’u wa at-taufiq reconciles conflicting evidence without nullifying either, while nasakh abrogates previous rulings for public interest, based on the sequence of revelation and God's will.